Acute toxicity of 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-thiol alkyl derivatives - Danilchenko, D. M.; Parchenko, V. V.; Данільченко, Дмитро Михайлович; Парченко, Володимир Володимирович (ЗДМУ, 2016)
Aim of our work was the further exploration of the new 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-thiol alkyl derivatives’ acute toxicity, setting some patterns of alkyl substituents influence by the Sulfur atom on the acute toxicity. Research materials and methods. In this study we used first time synthesized 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole- 3-thione derivatives. Acute toxicity was conducted on white rats weighing 160–250 g, which were injected once intraperitoneally with the investigated substances. The rats were received from the nursery of the Pharmacology and Toxicology Institute of Ukraine Medical Sciences Academy. The animals were kept on a standard diet with natural light mode “day-night”. Results and their discussion. After the acute toxicity studies in a group of 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole 3-alkyl derivatives it was found that among all studied structures the most toxic was 2e, LD50 of which was 263 mg/kg, and the least toxic compound was 2a, LD50 of which was 1570 mg/kg, that belongs to the V toxicity class. After comparing the acute toxicity of well-known antimycotic agent fluconazole with the studied compounds it can be argued that most compounds are less toxic than the comparison drug fluconazole with the index of LD50 ˃320 mg/kg. It was found that the transition in a group from butyl to decyl, octyl, ventyl, propyl, nonyl and heptyl substituents in the molecule of 3-alkylthio 5-(furan-2-yl)-4-amino-4H-1,2,4-triazole is accompanied by the toxicity increasing. Speaking about the 5-(2-metylfuran-3-yl)-4-amino-4H- 1,2,4-triazole 3-alkylthio derivatives we can find that this dependence is observed in a number from propyl, pentyl, nonil, butyl, heksyl, octyl and heptyl hydrocarbon chains. Conclusions. The investigated 3-alkylthio 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole derivatives belong to the IV-V toxicity class. The toxicity of 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole alkyl derivatives varies depending on the hydrocarbon substituents, so the presence of 3-heptylthiol substituent in the С3 atom at 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole leads to the toxicity increase. Introduction of 3-butylthiol to the molecule of 5-(furan-2-yl)-4-amino-4H-1,2,4-triazole, and the 3-propylthiol substituents in the 5-(2-metylfuran-3-yl)-4-amino-4H-1,2,4-triazole results the formation of lowest acute toxicity. Мета роботи – детально дослідити гостру токсичність нових алкілпохідних 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-1,2,4-тріазол-3-тіолів, встановити деякі закономірності впливу алкільних замісників по атому Сульфуру на показники гострої токсичності відповідних сполук. Матеріали та методи. У дослідженнях використані вперше синтезовані похідні 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазол-3-тіону. Оцінювання гострої токсичності здійснено на білих щурах масою 160–250 г, яким одноразово внутрішньочеревинно вводили досліджувані речовини. Щурів отримали з розплідника Інституту фармакології та токсикології АМН України. Тварини утримувалися на стандартному раціоні харчування, при природному світловому режимі «день – ніч». Результати. Після завершення експериментальних досліджень гострої токсичності в ряду 3-алкілтіопохідних 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу встановили, що найтоксичнішою сполукою серед досліджуваних виявилась сполука 2е, LD50 якої становила 263 мг/кг, а найменш токсичною – сполука 2а, LD50 котрої становить 1570 мг/кг, що належить до V класу токсичності сполук. Порівнюючи гостру токсичність відомого антимікотичного засобу флуконазолу з досліджуваними сполуками, можна стверджувати: більшість сполук, що досліджували, менш токсичні, ніж препарат порівняння флуконазол із показником LD50 ˃320 мг/кг. Встановили, що при переході в ряду від бутильного до децильного, октильного, вентильного, пропільного, нонільного та гептильного замісників у молекули 3-алкілтіо 5-(фуран-2-іл)-4-аміно-4Н-1,2,4-тріазолу зростає токсичність. Що ж стосується молекули 3-алкілтіопохідних 5-(2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу, то ця залежність спостерігається в ряду від пропільного, пентильного, нонільного, бутильного, гексильного, октильного та гептильного вуглеводневих ланцюгів. Висновки. Досліджувані похідні 3-алкілтіо 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу належать до сполук із IV–V класом токсичності. Токсичність 3-алкілпохідних 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу варіюється за¬лежно від вуглеводневих замісників. Так, наявність 3-гептилтіольного замісника за С3 атомом 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу призводить до зростання їхньої токсичності. Введення до молекули 5-(фуран-2-іл)-4-аміно-4Н-1,2,4-тріазолу 3-бутилтіольного, а до 5-(2-метилфуран-3-іл)-4-аміно-4Н-1,2,4-тріазолу 3-пропілтіольного замісників призводить до формування найнижчих показників гострої токсичності.
Гостра токсичність алкілпохідних 5-(фуран-2-іл, 2-метилфуран-3-іл)-4-аміно-1,2,4-тріазол-3-тіолів
Keywords: acute toxicity; 1,2,4-triazoles; activity; гостра токсичність; 1,2,4-тріазоли; активність; LD50